Oral contraceptive pills shortage in Lebanon amidst the economic collapse: a nationwide exploratory study - Rania Itani; Hani MJ Khojah; Samar Karout; Rana Abu-Farha; Tareq L. Mukattash; Deema Rahme; Khouloud Housary; Hiam El Achi; Ali O. Safar; Ismail Karam Al Hajj; Abdalla El-Lakany (BMC, 2023)
Abstract Background The political instability, economic crisis, and devaluation of the national currency left Lebanese females suffering from a scarcity of oral contraceptive pills (OCPs). Therefore, we aimed to identify the incidence of OCPs shortage in Lebanon and its impact on women's sexual and reproductive health, as well as physical and psychological well-being. Methods Community pharmacies were selected randomly across Lebanon, using a stratified sampling approach, where female clients asking for OCPs were interviewed using a standardized data collection form. Results A total of 440 females were interviewed. More than three-quarters of the participants (76.4%) reported not finding their preferred OCPs brands, almost 40% were affected by the increased prices, and 28.4% declared stockpiling OCPs. More than half of the participants using OCPs for pregnancy prevention reported adopting alternative traditional contraceptive methods (55.3%). Unplanned pregnancy was reported by 9.5% of participants, where 75% of them disclosed intentional abortion while the remaining (25%) reported experiencing a spontaneous miscarriage. Other consequences of OCPs shortage included mood disturbances (52.3%), dysregulation of menses (49.7%), dysmenorrhea (21.1%), weight gain (19.6%), acne (15.7%), and hirsutism (12.5%). Of the participants taking OCPs for birth control, 48.6% reported a reduced frequency of sexual intercourse, which led to conflicts with their partners (46%) and a decreased libido (26.7%). Conclusions OCPs shortage has seriously and negatively exposed women to various undesirable consequences including unplanned pregnancy and dysregulation of menses. Therefore, there is an urgent need to bring the attention of healthcare authorities to support the national pharmaceutical industry in manufacturing affordable OCPs generics to meet women's reproductive health demands.